Ginsenoside Ro prevents endothelial injury via promoting Epac1/AMPK- mediated mitochondria protection in early diabetic retinopathy - Jia Liu; Yunqi Zhang; Xiaoyu Xu; Xi Dong; Yunfeng Pan; Xiaobo Sun; Yun Luo (Pharmacological Research)
Diabetic retinopathy (DR) is a blinding complication of microangiopathy. First-line therapeutic drugs are all focused on late-stage DR and have several side effects, which could not meet clinical needs. The plant-derived ginsenoside Ro (Ro) has a variety of effective anti-inflammatory, immune-regulating, and cardiovascular protective effects, but its microvascular protective effects are rarely studied. This study aimed to explore the protective effect and mechanism of Ro on retinal microvascular endothelial cells in early stage of DR. We demonstrated that Ro exerted endothelial cell protection by regulating mitochondrial oxidative stress and autophagy in AGEs-injured endothelial cells. Moreover, Ro alleviated DR progress through improving retinal thickness and pathological changes in STZ-induced diabetic mice. Mechanically, Ro promotes the activation of Epac1-mediated AMPK signaling. On the contrary, the protective effects of Ro were abolished by Epac1 inhibitor in vitro or Epac1 knock down in vivo. Our results revealed the important role of Ro on the treatment of DR and suggested that targeting Epac1 may be a promising approach to prevent and treat DR.